[Photograph of WWII Memorial to Forced Labor Victims] - Streng, Evelyn Fiedler (1987)
Photograph of WWII memorial to the Forced Labor Victims in Friedhof Ammerthal Cemetary. Five, detached stone signs list countries that were victims of forced labor in WWII. Fifteen countries are listed including Belgium, Bulgaria, Czechoslovakia, Germany, France, Greenland, Italy, Yugoslavia, The Netherlands, Austria, Poland, Romania, Spain, Hungary, and the Soviet Union.